Short Implants in Partially Edentulous Maxillae and Mandibles: A 10 to 20 Years Retrospective Evaluation - Diego Lops; Eriberto Bressan; Gianluca Pisoni; Niccolò Cea; Boris Corazza; Eugenio Romeo (International Journal of Dentistry)
Purpose. Evaluation of the short implant (8 mm in height) long-term prognosis and of the implant site influence on the prognosis. Methods. A longitudinal study was carried out on 121 patients (57 males and 64 females) consecutively treated with 257 implants. 108 implants were short. Results. Four (3.6%) short implants supporting fixed partial prostheses failed. Similarly, three standard implants supporting fixed partial prostheses and one supporting single-crown prosthesis failed. Mean marginal bone loss (MBL) and probing depth (PD) of short and standard implants were statistically comparable (P>.05). The 20-year cumulative survival rates of short and standard implants were 92.3 and 95.9%, respectively. The cumulative success rates were 78.3 and 81.4%. The survival rates of short implants in posterior and anterior regions were comparable: 95 and 96.4%, respectively. The difference between survival rates was not significant (P>.05). Conclusions. The high reliability of short implants in supporting fixed prostheses was confirmed. Short and standard implants long-term prognoses were not significantly different. The prognosis of short implants in posterior regions was comparable to that of in anterior regions. Nevertheless, a larger sample is required to confirm this trend.